Molecular detection of Dorylaimus stagnalis (Durjan, 1845), in the rhizosphere of soybean plants in Jember District, Indonesia - ANKARDIANSYAH PANDU PRADANA; ZIDNA NURUL IZZATIKA; HARDIAN SUSILO ADDY (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Pradana AP, Izzatika ZN, Addy HS. 2025. Molecular detection of Dorylaimus stagnalis (Durjan, 1845), in the rhizosphere of soybean plants in Jember District, Indonesia. Biodiversitas 26: 1913-1919. Nematodes, members of the phylum Nematoda, are ubiquitous soil organisms whose community composition provides critical insights into soil health and ecosystem function. The genus Dorylaimus is of particular ecological interest due to its adaptability and role in nutrient cycling within diverse terrestrial environments. This study documents the first molecular and morphometric confirmation of Dorylaimus stagnalis (Dujardin, 1845), in the rhizosphere of soybean (Glycine max) in Jember District, Indonesia. Soil samples were systematically collected from 15 distinct sites within soybean fields using a standardized protocol, and nematodes were extracted via the Whitehead tray method. Detailed morphological observations were made using an Olympus BX50 light microscope, and morphometric measurements were obtained following De Man’s ratios, which collectively confirmed diagnostic features consistent with D. stagnalis as reported in previous studies. Molecular characterization was performed by PCR amplification of the 28S-D2D3 region followed by Sanger sequencing. Subsequent phylogenetic analysis revealed 94% sequence similarity to established reference sequences (AY592994.1 and AY592995.1) and a low genetic distance of 0.1058, thereby substantiating the taxonomic identity of the specimens. This study’s integrative approach not only verifies the presence of D. stagnalis in Indonesia but also indicates subtle morphometric variations potentially attributable to local environmental pressures. Its findings expand the current understanding of nematode biodiversity in Indonesian agroecosystems and provide a framework for future research on sustainable soil management practices.